Transformations and Decomposition of MnCO3 at Earth's Lower Mantle Conditions - Boulard, Eglantine; Liu, Yijin; Koh, Ai L.; Reagan, Mary M.; Stodolna, Julien; Morard, Guillaume; Mezouar, Mohamed; Mao, Wendy L. (Frontiers in Earth Science, 2016)
Carbonates have been proposed as the principal oxidized carbon-bearing phases in the Earth's interior. Their phase diagram for the high pressure and temperature conditions of the mantle can provide crucial constraints on the deep carbon cycle. We investigated the behavior of MnCO3 at pressures up to 75 GPa and temperatures up to 2200 K. The phase assemblage in the resulting run products was determined in situ by X-ray diffraction (XRD), and the recovered samples were studied by analytical transmission electron microscopy (TEM) and X-ray absorption near edge structure (XANES) imaging. At moderate temperatures below 1400 K and pressures above 50 GPa, MnCO3 transformed into the MnCO3-II phase, with XANES data indicating no change in the manganese oxidation state in MnCO3-II. However, upon heating above 1400 K at the same pressure conditions, both MnCO3 and MnCO3-II undergo decomposition and redox reactions which lead to the formation of manganese oxides and reduced carbon.